An experimental investigation of the performance boundaries of a solar water heating system - Eleftheriou, Polyvios; Michaelides, Ioannis (My University, 2011)
This paper presents the performance characteristics of a solar water heating system consisting of a 3 m2 flat plate collector and a 68 L tank, from readings taken over a period of 2 years under real weather conditions. It focuses on the characteristics and the behavior of the system, its response to solar radiation and hot water flow rate through the collector under no load conditions and in the evaluation of the errors associated with the system performance measurements. The system behavior proved to be linear with small relative standard deviations (less than 15%) within the values of the calculated errors and also relatively insensitive to solar radiation fluctuations ranging from 800 to 1100 W/m2. Flow rate variations from 0.07 and up to 0.25 L/s did not produce any noticeable effects on the energy collected in the storage tank of the system under investigation. The calculated absolute errors in the system instantaneous efficiency ranged from 34% for low flow and up to 20% for the high flows.
Keywords: Solar water heating; Solar collector; Collector efficiency; Thermal energy storage; Thermal stratification; Solar system error analysis